Sistem Informasi Penjadwalan Latihan dan Kunjungan Penyuluh Pertanian (SIJALUTANI) - Faisal Muttaqin; Hendra Maulana; Gusti Eka Yuliastuti (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2022)
The rapid development of information technology can affect all aspects of daily life. One example is information systems. An information system is very important because it can make it easier for us to get the information we need. This is an abstract version of the Indonesian language. The Department of Food Security and Agriculture of Bojonegoro Regency is one of the agencies that needs to implement an information system related to scheduling agricultural extension workers because there is a problem where the scheduling of training and visits of agricultural instructors is done manually. Making an information system is a solution to the problems experienced. The information system that will be created by the author is named SIJALUTANI, where the name is an abbreviation of the Information System for Scheduling Training and Agricultural Extension Visits. The model applied to this information system is using the Waterfall Model.